2020
DOI: 10.1021/jasms.9b00065
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Determination of Polypeptide and Oligosaccharide Connectivities by Energy-Resolved Collison-Induced Dissociation of Protonated O-Glycopeptides Derived from Nonspecific Proteolysis

Abstract: Collision-induced dissociation (CID) is by far the most broadly applied dissociation method used for tandem mass spectrometry (MS/MS). This includes MS/MS-based structural interrogation of glycopeptides for applications in glycoproteomics. The end goal of such measurements is to determine the monosaccharide connectivity of the glycan, the amino acid sequence of the peptide, and the site of glycosylation for each glycopeptide of interest. In turn, this allows inferences with respect to the glycoprofile of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…Tandem mass spectrometry (MS) is the premier method for O-glycosite mapping, but O-glycopeptides are largely intractable using standard glycoproteomic approaches, which have focused almost entirely on N-glycans. To this end, recent efforts have focused on improving O-glycopeptide analyses, [7][8][9][10] ranging from developments in sample preparation, [11][12][13][14][15] data acquisition, [16][17][18][19][20][21] and post-acquisition data analysis. [22][23][24][25][26][27] One promising avenue to emerge from these investigations is the description of O-glycoproteases that can generate O-glycopeptides more amenable to MS characterization.…”
mentioning
confidence: 99%
“…Tandem mass spectrometry (MS) is the premier method for O-glycosite mapping, but O-glycopeptides are largely intractable using standard glycoproteomic approaches, which have focused almost entirely on N-glycans. To this end, recent efforts have focused on improving O-glycopeptide analyses, [7][8][9][10] ranging from developments in sample preparation, [11][12][13][14][15] data acquisition, [16][17][18][19][20][21] and post-acquisition data analysis. [22][23][24][25][26][27] One promising avenue to emerge from these investigations is the description of O-glycoproteases that can generate O-glycopeptides more amenable to MS characterization.…”
mentioning
confidence: 99%
“…Numerous alternative strategies enrich glycopeptides from whole cell or tissue lysate, but such approaches do not provide evidence for subcellular localization akin to that provided by the cell surface glycoprotein focused methods [ 55 , 66 , 108 , 110 , 113 , 118 , 120 ]. Methods for intact glycopeptide analysis by MS enable determination of monosaccharide compositions present at specific sites on a protein, but do not typically generate sufficient information to fully characterize glycan structures or structural isomers [ 36 , 43 , 44 , 50 , 86 , 94 , 97 ].…”
Section: Expanding the Assessment Of Protein Glycosylation In Hpsc-cmmentioning
confidence: 99%
“…This supports a recent report by Kelly and Dodds, where they found that O-glycopeptides require lower collision energies for precursor depletion for a small pool of O-glycopeptides. 88 Although some increase in Figures S14-S16 provide distributions of precursor peptide lengths, m/z values, and charge state distributions of identified N-and O-glycoPSMs for each method. As expected, EThcD methods extend the m/z range of ETD for successfully identified glycopeptides, making their distributions more similar to HCD and EThcD methods.…”
Section: Comparisons Between N-and O-glycopeptide Datamentioning
confidence: 99%
“…In 2017, Liu et al used sceHCD methods for identification of ~10,000 N-glycosites from five mouse tissues, 78 which contributed to its popularity in recent N-glycopeptide analysis. [79][80][81][82][83][84][85][86] A few studies have looked to extend the application of sceHCD to O-glycopeptides, 75,76,79,87,88 but this has not been as widespread. Limited comparisons between sceHCD and ETD methods have been performed for N-glycopeptides, 78 as have comparisons of HCD and EThcD for Oglycopeptides; 64,69 however, a comprehensive head-to-head comparison of standard HCD, sceHCD, ETD, and EThcD has not been reported.…”
Section: Introductionmentioning
confidence: 99%